Case Report: Combined perioperative extracorporeal membrane oxygenation for acute heart failure caused by mitral regurgitation - Daughtry, Brock; Richardson, John (Frontiers in Cardiovascular Medicine, 2024)
Abstract Extracorporeal membrane oxygenation (ECMO) and extracorporeal life support (ECLS) devices are well established adjunctive treatment measures for patients with heart failure. ECMO can serve as a bridge to transplant in the chronic setting or as a salvage therapy for patients who are unable to be weaned from bypass following cardiac surgery. The role of ECMO as a bridge to definitive therapy in the setting of acute heart failure is less established. Similarly, the treatment of patients using combined ECMO and ECLS devices has been, at times, shown to show some benefit however these benefits have not been widely studied. Presented here is a patient who was diagnosed with severe acute onset heart failure secondary to torrential mitral regurgitation following COVID-19 pneumonia. The patient was emergently placed on venoarterial (VA) ECMO with an indwelling centrifugal pump device in the left ventricle. This combination of ECMO and ECLS served as a bridge to open mitral valve replacement six days after presentation. Following successful mitral valve replacement, the patient had persistent right ventricular failure, so the decision was made to incorporate venovenous (VV) ECMO into the VA ECMO circuit. This technique, resulted in a VV-VA, or VPa-VA configuration as oxygenated blood was being returned to the pulmonary artery as well as the descending aorta. VA ECMO was discontinued after four days of therapy, and the patient was extubated three days later. VV ECMO was weaned over the following week, and the patient was decannulated after 23 total days of ECMO. The patient was then transitioned to inpatient rehabilitation and ultimately discharged home after 18 days. At 6 months follow up, the patient is doing well and objective cardiopulmonary testing reveal normal function. This case is an excellent demonstration of how advanced ECMO and ECLS devices can be used in unique ways through multiple configurations to rescue and optimize patients in the perioperative period.